2021
DOI: 10.3390/foods10092223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Different Dietary Patterns on Breast Cancer: Monitoring Circulating Tumor Cells

Abstract: The occurrence and development of breast cancer are closely related to dietary factors, especially dietary patterns. This study was to investigate the effects of dietary patterns on the process of tumor metastasis by in vivo circulating tumor cell (CTC) capture strategy and monitoring changes of CTC numbers in breast tumor mice model. Meanwhile, the effects of different dietary patterns on the development of lung metastases of breast cancer and the volume and weight of carcinoma in situ were investigated. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…[213][214][215] In mice, an HSD accelerated the development and lung metastasis of breast cancer. 152,216 Data suggested that the IL-17F produced by salt-induced Th17 cells activated the MAPK signalling in breast cancer cells. 152 In humans, high salt intake is a risk factor for lung, testicular, bladder, 182 renal cell, 183 pancreatic, 184 oesophageal 181 and gastric cancer.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[213][214][215] In mice, an HSD accelerated the development and lung metastasis of breast cancer. 152,216 Data suggested that the IL-17F produced by salt-induced Th17 cells activated the MAPK signalling in breast cancer cells. 152 In humans, high salt intake is a risk factor for lung, testicular, bladder, 182 renal cell, 183 pancreatic, 184 oesophageal 181 and gastric cancer.…”
Section: Cancermentioning
confidence: 99%
“…In vitro, high salt can synergize with IL‐17 to enhance the proliferation, treatment resistance and Warburg‐like metabolism of breast cancer cells 213–215 . In mice, an HSD accelerated the development and lung metastasis of breast cancer 152,216 . Data suggested that the IL‐17F produced by salt‐induced Th17 cells activated the MAPK signalling in breast cancer cells 152 .…”
Section: The Effect Of High‐salt Diet On Immune‐regulated Diseasesmentioning
confidence: 99%
“…We can also envisage that the membrane profile and remodeling by membrane lipid therapy becomes strategically important in combination with early diagnostic tools, which are proposed for prognostic screening and prevention of cancer, such as circulating cancer cells [ 96 , 97 ]. Literature evidence in favor of the holistic vision in cancer suggests such a development to be strategic for early cancer diagnostic approaches, at a stage where chemotherapeutic treatments cannot be prescribed to the patient, whereas diets can be important tools for active prevention, including fatty acid-based strategies [ 98 ].…”
Section: Applications Of Fatty Acids As Nutraceuticals To Cancer Ther...mentioning
confidence: 99%
“…In a study of nude mice injected with a gastric adenocarcinoma cell line, mice fed a KD had significantly delayed tumor growth compared with those fed a standard diet [46]. In a separate study, mice inoculated with the 4T1 breast cancer cell line were given a KD or control diet; those that consumed the KD had lower levels of circulating tumor cells, which correlated with lower metastatic disease burden [47]. Although not induced by diet, exogenous ketone supplementation with either 1,3-butanediol or a ketone ester decreased proliferation and viability of cultured cancer cells in vitro and prolonged survival in vivo in mice implanted with firefly luciferase-tagged syngeneic VM-M3 cells (a metastatic cancer model), independent of glucose levels [48].…”
Section: The Effects Of Insulin-lowering Diets On Metastasis In Anima...mentioning
confidence: 99%